Addressing the Continuing Conundrum of Research and Practice. (May 2019) - Boone, Randall; Higgins, Kyle
This is the introduction to a special issue focusing directly on the underlying principles that guide the editorial focus of Intervention in School and Clinic ( ISC ), that of the relationship between research and practice. Eight articles written by Associate Editors of ISC explicate and extend the significant issues facing both the research and practitioner communities in furthering the initiative of translating genuine, positive research outcomes to clearly articulated tactics and strategies for effective implementation.